3-(1-Hydroxy-2-phenylprop-2-en-1-yl)phenol - Caracelli, Ignez [UNESP]; Zukerman-Schpector, Julio; Singh, Fateh V.; Stefani, Helio A.; Tiekink, Edward R. T. (Wiley-Blackwell, 2010)
Two independent pseudo-enantiomeric molecules comprise the asymmetric unit in the title compound, C(15)H(14)O(2). While the central O-C-C-C residue approaches planarity [torsion angles = -15.8 (3) (molecule a) and 15.4 (3)degrees (molecule b)], the benzene rings are approximately orthogonal [the dihedral angles formed between the benzene rings are 62.89 (12) (molecule a) and 80.15 (12)degrees (molecule b)]. Two-dimensional arrays in the ab plane sustained by O-H center dot center dot center dot O hydrogen bonding are found in the crystal structure.